INEXHAUSTIBLE - Fischlin, Daniel; Heble, Ajay; Melville, Lewis; Warren, Ted; Copping, Aimee (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
This piece was originally screened during IF 2022. Videography art by Aimee Copping. Vertical Squirrels is Daniel Fischlin, Ajay Heble, Lewis Melville, and Ted Warren.